Kajian Materi Pendidikan Agama Islam dengan Pendekatan Psikologi - Darmawati Jufri; Tobroni Tobroni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article examines Islamic Religious Education (PAI) materials through a psychological approach to optimize students' understanding of religious teachings. This study explores five main aspects: (a) religion from psychologists' perspective which emphasizes the role of religion in identity formation and psychological well-being, (b) adaptation of PAI materials according to students' developmental stages, which is essential to ensure religious teachings can be well received and understood, (c) analysis of PAI materials based on interests and talents, focusing on increasing student motivation and engagement, (d) PAI models oriented towards religious comfort, which aims to create positive relationships between students and religious teachings, and (e) the role of PAI teachers as spiritual counselors who support students' mental and spiritual health. With this approach, religious education can function as both a spiritual foundation and sustainable psychological support. This article is expected to serve as a reference for educators and education practitioners in developing more effective and relevant PAI materials.